Advances in laparoscopic surgery for cervical cancer. (November 2019) - Bogani, Giorgio; Maggiore, Umberto Leone Roberti; Rossetti, Diego; Ditto, Antonino; Martinelli, Fabio; Chiappa, Valentina; Ferla, Stefano; Indini, Alice; Sabatucci, Ilaria; Lorusso, Domenica; Raspagliesi, Francesco
Graphical abstract: Abstract: In the recent years, minimally invasive surgery has emerged as the gold standard for the treatment of both benign and malignant gynecological conditions. Growing evidence suggest that laparoscopic and robotic-assisted treatments allow to archived the same long-term outcomes than conventional open abdominal treatments, minimizing peri-operative morbidity. In the present review we analyzed the advances in the treatment of cervical cancer patients, reporting the advances in both the evolution of concept of radical hysterectomy and of the adoption of minimally invasive surgery. We discussed the advantages related to the introduction of minimally invasive treatment for cervical cancer patients; innovation of conventional laparoscopic surgery as discussed as well. Recent evidence suggested a potential detrimental effect on long-term survival outcomes related to the use of minimally invasive surgery in patients affected by cervical cancer. However, reasons why minimally invasive surgery might have a detrimental effect are still unclear. Further evidence is needed in order to improve quality of treatment for cervical cancer patients.